Application of Activated Carbon Compost Raw Material As Adsorbent For Removal Of Peat Water Dyes - Desmawita, Dwi; Yenie, Elvi; Daud, Syarfi (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2018)
Peat water has a low pH (3-5), brown (124-850 PtCo), and contains many organic substances that do not meet the standards of water quality requirements as Permenkes No.416/MENKES/PER/IX/1990. Therefore it is necessary for processing methods to eliminate pollutants contained in the peat water so it can be used according to quality standards, either by adsorption. Adsorbent used in this research is compost. Compost carbonized by variation of 30, 60 and 90 minutes, which is activated in physics at a temperature of 500 ° C. Adsorbent mass variations as much as 1, 2, 3, 4 and 5 grams with a stirring speed of 100 rpm for 120 minutes. Characteristics of activated carbon in the form of compost moisture content, ash content, volatile and fixed carbon content obtained the best results in 60 minutes with a water content of 4.00%; ash content 0.99% volatile 1.57% and fixed carbon 97.44%. The efficiency of color reduction was measured using a UV-VIS spectrophotometer. The result showed that the highest efficiency was 81,63% at carbonization time 60 minutes with mass 5 gram and the lowest efficiency value was 66,57% at carbonization time 30 minutes with mass 1 gram.Keywords : Adsorbent, activated carbon, compost, color.